Catalyst mesh comprising noble metal wires made of dispersion-strengthened noble metal alloy
By integrating dispersion-strengthened precious metal alloys with zirconium, cerium, or yttrium oxides into the catalyst mesh wires, mechanical stability and catalytic efficiency are enhanced, addressing the issues of compression and longevity in flow reactors.
Patent Information
- Application Number
- CN202380041335.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-25
- Filing Date
- 2023-02-27
- Publication Date
- 2024-12-31
AI Technical Summary
Catalyst meshes in flow reactors experience reduced efficiency due to compression and mechanical instability at high temperatures, leading to decreased free surface area and altered flow conditions, which is economically unattractive and affects the overall process efficiency.
Incorporating dispersion-strengthened precious metal alloys, such as those containing zirconium, cerium, scandium, or yttrium oxides, into the precious metal wires to enhance mechanical stability and maintain catalytic activity.
The use of dispersion-strengthened precious metal alloys significantly increases the useful life of the catalyst mesh by reducing compression and maintaining high catalytic efficiency, even at elevated temperatures.
Smart Images

Figure CN119233864A_ABST
Abstract
Description
[0001] The invention relates to a catalyst mesh comprising at least one noble metal wire containing at least one dispersion-strengthened noble metal alloy. The invention also relates to a catalyst system containing at least one catalyst mesh according to the invention and to a method for the catalytic oxidation of ammonia in which the catalyst mesh according to the invention is used.
[0002] Catalyst nets are particularly used in flow reactors for gas reactions. They are used, for example, for the preparation of hydrocyanic acid by the Andrussow process or for the preparation of nitric acid by the Ostwald process. Suitable catalysts must provide a large catalytically active surface. Therefore, generally speaking, a catalyst net in the form of a three-dimensional, air-permeable structure of precious metal wires is used. Collection systems for recovering evaporated catalytically active components are also often based on this grid structure. Usually, a plurality of nets are advantageously arranged one after another and combined to form a catalyst system. The catalyst system consists of 3 to 50 catalyst nets stacked one above the other, wherein the number depends substantially on the conditions in the reactor, such as the operating pressure and mass flow rate of the gas. The diameter of the net reaches 6m in some burners.
[0003] Catalyst net is usually composed of a single layer or multilayer net in the form of a braided fabric and / or a woven fabric. A separate net is made of a fine noble metal wire mainly containing platinum (Pt), palladium (Pd), rhodium (Rh) or an alloy of these metals. The selection of the material of the noble metal wire is particularly determined by the position and function of the catalyst net in the catalyst system. Specifically, in addition to the noble metal, the capture net may also contain other ingredients, such as nickel. In order to increase the available surface for catalytic activity, the catalyst net usually has a three-dimensional structure, except for their planar extension.
[0004] The catalyst mesh is used at high temperature (>800°C) in the reactor. Due to the pressure difference and high temperature in the reactor, the mesh structure is compressed, which not only reduces the free surface area accessible to the reactants, but also reduces the flow conditions. These effects cause the efficiency to decrease with the increase of the duration of use. Due to the high precious metal prices, it is economically unattractive to produce catalyst meshes from thicker and therefore stronger precious metal wires. In addition, this is technically unattractive because the pressure drop increases with the increase of the wire diameter, which will have an adverse effect on the overall efficiency of the process. Therefore, it is desirable to optimize the mechanical stability of the catalyst mesh and the amount of precious metals for a given catalytic activity. Another problem that may occur during ammonia oxidation is the fusion and / or sintering of multiple catalyst meshes arranged front and back.
[0005] In the prior art, the improvement of the mechanical stability of the catalyst mesh is usually achieved by the shape of the precious metal wire used. For example, EP 0652985 A1 discloses a wire made of a platinum compound, which includes at least one helical subsection. In EP 3523024 A1, in order to increase the mechanical strength of the catalyst mesh, it is proposed to use a wire made of a plurality of filaments twisted together to produce them.
[0006] In order to increase the strength of the catalyst mesh, EP 3256244 A1 proposes the use of a three-dimensional structure in which a plurality of catalyst mesh layers are connected to one another via so-called pole threads.
[0007] The solutions disclosed in the prior art therefore require a more complex production of the noble metal wires or catalyst meshes.
[0008] If metallic materials contain small amounts of insoluble particles of base metal oxides uniformly distributed therein, they generally have a higher heat resistance. Such materials are called dispersion strengthened or dispersion hardened. The production can be carried out using different methods (see in particular the production of platinum-based materials: E.Drost, H. M. Poniatowski, S. Zeuner: Platinum Materials for High-temperature Use, Metall 50 (1996), 492-498). Dispersion-strengthened platinum materials are characterized, for example, by their corrosion resistance and oxidation resistance at high temperatures and are used in the glass industry, in particular due to their resistance to glass melts. The production and processing of these materials are described, for example, in the publications GB 1340076 A, EP 0683240 A2, EP 1188844 A1, EP 1964938 A1 and EP 3077556 A1. However, their use for catalyst meshes is unknown.
[0009] The object of the present invention is to overcome some of the disadvantages of the prior art. The object is to provide a catalyst mesh which ensures a high product yield which is also stable over time while also having a long service life. In particular, an object of the present invention is to provide a catalyst mesh which has reduced compression under conditions for use in a flow reactor in order to ensure increased long-term stability.
[0010] This object is achieved by a catalyst mesh comprising at least one precious metal wire, characterized in that the at least one precious metal wire contains at least one dispersion-strengthened precious metal alloy, which precious metal alloy, in addition to at least one precious metal, also contains at least one non-precious metal, wherein the at least one non-precious metal is selected from the group consisting of the following items: zirconium, cerium, scandium and yttrium, and the at least one non-precious metal is at least partially present as an oxide.
[0011] The invention also provides catalyst systems and methods for using such catalyst meshes.
[0012] Surprisingly, it has been found that by using a dispersion strengthened precious metal alloy for at least one precious metal wire of the catalyst mesh, the useful life of the mesh can be significantly increased while maintaining the same catalytic efficiency. Without wishing to be bound by any theory, the use of dispersion strengthened precious metal wires in the manufacture of the mesh may result in higher mechanical strength at high operating temperatures, which may result in reduced compression during the useful life.
[0013] The present invention relates to a catalyst mesh. The catalyst mesh should be understood to mean a single-layer or multi-layer air-permeable fabric. The surface formation of the catalyst mesh is achieved by interweaving one or more noble metal threads to form a mesh. The catalyst mesh can be produced, for example, by weaving, interweaving or braiding one or more noble metal threads. The structure of the catalyst mesh can be set in a targeted manner by using different weaving or braiding patterns and / or different mesh sizes.
[0014] Catalyst mesh is usually used in flow reactors. The catalyst mesh is installed in the reaction zone in a plane perpendicular to the fresh gas flow direction.
[0015] In a preferred embodiment, the catalyst net can include a three-dimensional structure. In the context of the present application, the net is understood to be a flat, two-dimensional object. The three-dimensional structure is understood to mean that the catalyst net also includes an extension to the third spatial dimension except that it is planar and two-dimensionally extended. The catalyst net with a three-dimensional structure has a larger free surface area and better material transport conditions between gas and surface, which advantageously affects the catalytic effectiveness and can reduce the pressure drop in the flow reactor. The three-dimensional structure can be obtained by using at least one precious metal wire with two-dimensional or three-dimensional structure or by texturing the catalyst net. The three-dimensional structure of the catalyst net can be, for example, a waveform or coil-shaped. In order to produce this structure, the catalyst net of the original plane can be subjected to a process step in which the three-dimensional structure is stamped or produced by folding.
[0016] The catalyst mesh contains at least one noble metal wire. A noble metal wire is understood to be a wire consisting of a noble metal or a noble metal alloy. A noble metal alloy is understood to mean an alloy consisting of a noble metal to an extent of more than 50% by weight. The fact that an alloy consists of more than 50% by weight of a noble metal means that the weight proportion of the noble metal is at least 50% by weight of the total alloy weight.
[0017] The noble metal is preferably selected from platinum metal, gold and silver. Platinum metal is understood to mean the so-called platinum group metals, ie platinum (Pt), palladium (Pd), iridium (Ir), rhodium (Rh), osmium (Os) and ruthenium (Ru).
[0018] The at least one precious metal wire comprises at least one dispersion strengthened precious metal alloy.
[0019] The dispersion-strengthened precious metal alloy may contain a single precious metal or a combination of precious metals. Preferably, the dispersion-strengthened precious metal alloy is composed of at least 50% by weight, particularly preferably at least 70% by weight, in particular at least 90% by weight, and most preferably at least 99% by weight of at least one precious metal, based on the total weight of the dispersion-strengthened precious metal alloy.
[0020] Preferably, the at least one noble metal of the dispersion strengthened noble metal alloy is selected from the group consisting of platinum, palladium, rhodium and mixtures thereof.
[0021] Particularly preferably, at least one of the noble metals of the dispersion-strengthened noble metal alloy is platinum; in this case, the dispersion-strengthened noble metal alloy is a dispersion-strengthened platinum alloy. Particularly advantageously, the dispersion-strengthened platinum alloy consists of at least 50% by weight, preferably at least 70% by weight, particularly preferably at least 80% by weight of platinum.
[0022] In addition, the dispersion-strengthened platinum alloy may also contain at least one other noble metal. Such dispersion-strengthened platinum alloys preferably contain at least 70% by weight of platinum and at most 29.95% by weight of at least one other noble metal, in particular at least 80% by weight of platinum and at most 19.95% by weight of at least one other noble metal. The at least one other noble metal is preferably selected from the group consisting of ruthenium, rhodium, gold, palladium, iridium and mixtures thereof. Preferably, the dispersion-strengthened platinum alloy is a platinum-rhodium alloy, a platinum-gold alloy, a platinum-palladium alloy, a platinum-palladium-rhodium alloy or a platinum-iridium alloy.
[0023] The dispersion strengthened precious metal alloy comprises at least one non-precious metal selected from the group consisting of zirconium, cerium, scandium, and yttrium.
[0024] Preferably, the dispersion-hardened precious metal alloy contains 0.005 to 1.0 wt. %, particularly preferably 0.1 to 0.8 wt. % and especially preferably 0.2 to 0.5 wt. % of at least one non-precious metal, based on the total weight of the dispersion-hardened precious metal alloy.
[0025] The at least one non-precious metal exists at least partially as an oxide. A prerequisite may be that the at least one non-precious metal is at least 70% oxidized, preferably at least 90%, particularly preferably 99% and particularly preferably fully oxidized. Here, all oxidation states of the at least one non-precious metal are taken into account, so that preferably at most 30%, particularly preferably at most 10%, and in particular at most 1% of the at least one non-precious metal exists as a metal, that is, exists in the form of 0 oxidation state. The ratio of the at least one non-precious metal present as an oxide gives the ratio between the amount of the at least one non-precious metal in an oxidation state higher than 0 and the total amount of the at least one non-precious metal. The ratio of the at least one non-precious metal present as an oxide can be determined by carrier gas thermal extraction. For this purpose, the oxygen content is indirectly measured by reacting oxygen from the sample with carbon and using IR spectroscopy to quantify the content of the resulting CO2. The determination is based on the assumption that the entire oxygen content of the sample is attributed to the oxidized non-precious metal. In the case of a mixture of multiple non-precious metals, it is assumed that the ratio of oxidized and unoxidized non-precious metals is the same for different non-precious metals.
[0026] The oxide of the at least one non-noble metal is preferably in the form of particles uniformly dispersed in the noble metal matrix; the particles preferably have a size in the range of 1 nm to 1 μm, in particular in the range of 50 nm to 500 nm. Preferably, the particles are smaller than 1 μm, in particular smaller than 500 nm, particularly preferably smaller than 100 nm.
[0027] The at least one non-noble metal may also include a mixture of multiple non-noble metals. Preferred non-noble metal mixtures include yttrium and zirconium, yttrium and cerium, yttrium and scandium, zirconium and cerium, zirconium and scandium, cerium and scandium, yttrium, zirconium and cerium, or yttrium, zirconium and scandium.
[0028] Preferably, the proportion of zirconium in the mixture of multiple non-precious metals is in the range of 70 mol% to 98 mol%, more preferably in the range of 80 mol% to 95 mol%, particularly preferably in the range of 85 mol% to 93 mol%, and most preferably in the range of 90 mol% to 92 mol%.
[0029] The proportion of yttrium in the mixture of multiple non-precious metals is preferably in the range of 2 mol% to 30 mol%, more preferably in the range of 3.5 mol% to 20 mol%, particularly preferably in the range of 5 mol% to 15 mol%, and most preferably in the range of 6 mol% to 10 mol%.
[0030] The proportion of cerium in the mixture of multiple non-precious metals is preferably in the range of 2 mol% to 30 mol%, more preferably in the range of 3.5 mol% to 20 mol%, particularly preferably in the range of 5 mol% to 15 mol%, and most preferably in the range of 6 mol% to 10 mol%.
[0031] Preferred mixtures of non-noble metals consist of:
[0032] (a) 2 mol% to 30 mol%, preferably 7 mol% to 15 mol% of yttrium and 70 mol% to 98 mol%, preferably 85 mol% to 93 mol% of zirconium,
[0033] (b) 2 mol % to 30 mol %, preferably 7 mol % to 15 mol % of yttrium and 70 mol % to 98 mol %, preferably 85 mol % to 93 mol % of cerium,
[0034] (c) 2 mol% to 30 mol%, preferably 7 mol% to 15 mol% of cerium and 70 mol% to 98 mol%, preferably 85 mol% to 93 mol% of zirconium,
[0035] (d) 2 mol% to 30 mol%, preferably 3 mol% to 15 mol% of yttrium, 2 mol% to 30 mol%, preferably 3 mol% to 15 mol% of cerium and 40 mol% to 96 mol%, preferably 70 mol% to 94 mol% of zirconium,
[0036] (e) 2 mol% to 30 mol%, preferably 3 mol% to 15 mol% of yttrium, 2 mol% to 30 mol%, preferably 3 mol% to 15 mol% of scandium and 40 mol% to 96 mol%, preferably 70 mol% to 94 mol% of zirconium.
[0037] Preferably, the dispersion-strengthened precious metal alloy is a pure precious metal or a precious metal alloy in which only an at least partially oxidized non-precious metal is mixed in addition to impurities. In other words, the dispersion-strengthened precious metal alloy is preferably composed of at least one precious metal, at least one at least partially oxidized non-precious metal, and impurities; therefore, the dispersion-strengthened precious metal alloy is preferably composed of at least one precious metal, at least one non-precious metal, oxygen, and impurities.
[0038] Impurities of the dispersion-strengthened precious metal alloy and non-precious metals or their oxides are understood to mean conventional impurities which are intended to enter the dispersion-strengthened precious metal alloy or which inevitably enter the starting material during the preparation process or which cannot be (completely) removed from the raw materials with reasonable efforts. The impurity proportion preferably does not exceed 1% by weight, preferably not more than 0.5% by weight, of the described dispersion-strengthened precious metal alloy.
[0039] Particularly preferably, the dispersion-strengthened precious metal alloy is a dispersion-strengthened platinum alloy, i.e., pure platinum or a platinum alloy in which only at least partially oxidized non-precious metals are mixed in addition to impurities. In other words, the dispersion-strengthened platinum alloy preferably consists of platinum and optionally at least one other precious metal, at least one non-precious metal that is at least partially oxidized, and impurities; therefore, the dispersion-strengthened platinum alloy preferably consists of platinum and optionally at least one other precious metal, non-precious metal, oxygen and impurities. The impurity proportion preferably does not exceed 1% by weight, preferably not more than 0.5% by weight, of the described dispersion-strengthened platinum alloy in total. In a particularly preferred embodiment, the dispersion-strengthened platinum alloy consists of platinum, rhodium, at least one non-precious metal that is at least partially oxidized, and impurities.
[0040] Examples of preferred dispersion-strengthened platinum alloys are PtRh(1-20)NEM(0.005-1) alloys or PtPd(10-20)Rh(1-5)NEM(0.005-1) alloys, particularly preferably PtRh3NEM(0.005-1), PtRh4NEM(0.005-1), PtRh5NEM(0.005-1), PtRh8NEM(0.005 -1), PtRh10NEM (0.005-1), PtRh15NEM (0.005-1), PtPd5Rh5NEM (0.005-1), PtPd5Rh3NEM (0.005-1), PtPd5Rh4NEM (0.005-1), PtPd15Rh3NEM (0.005-1) or PtPd15Rh4NEM (0.005-1). PtRh(X)NEM(0.005-1) means that the alloy, in addition to impurities, also consists of X weight % rhodium, 0.005 to 1 weight % non-noble metal (NEM), at least partially oxidized oxygen of the non-noble metal, and platinum; PtPd(Y)Rh(X)NEM(0.005-1) means that the alloy, in addition to impurities, also consists of Y weight % palladium, X weight % rhodium, 0.005 to 1 weight % non-noble metal (NEM), at least partially oxidized oxygen of the non-noble metal, and platinum.
[0041] The oxide of at least one non-precious metal may be added to the precious metal or precious metal alloy during the production of the dispersion-strengthened precious metal alloy. Alternatively, the oxide of the at least one non-precious metal may be formed in situ by partially oxidizing the at least one non-precious metal during the preparation of the dispersion-strengthened precious metal alloy.
[0042] Dispersion strengthened precious metal alloys can be produced by powder metallurgy or melt metallurgy.
[0043] For the powder metallurgical production of dispersion strengthened precious metal alloys, for example, a powder of the precious metal composition can be mechanically mixed with a powder of an oxide of at least one non-precious metal. Powder metallurgical production can also be carried out by simultaneous precipitation from a salt solution, by evaporation of a solution containing at least a precursor of the desired components, or by spraying such a solution into a flame. Additional manufacturing steps can include annealing the powder, pressing it into a mold, and sintering.
[0044] Preferably, it can be a prerequisite that a precious metal alloy is first produced by melt metallurgy, the alloy comprising at least one precious metal and at least one non-precious metal. This can then be followed by an oxidation step, in which the at least one non-precious metal contained in the precious metal alloy is at least partially oxidized by heat treatment in an oxidizing medium. The dispersion-strengthened precious metal alloy produced in this way can then be formed into precious metal wires and particularly preferably annealed before and / or afterward.
[0045] The catalyst mesh according to the invention comprises at least one noble metal wire. The catalyst mesh may consist entirely of noble metal wires, but it may also comprise other components, such as wires or yarns made of non-noble metals or non-metallic materials. Examples of non-metallic materials are organic materials and ceramic materials.
[0046] Preferably, noble metal wires are used having a diameter of 40 to 150 μm, preferably 50 to 130 μm.
[0047] The at least one noble metal wire can be designed as a round wire, ie with a round cross section. In another embodiment, the at least one noble metal wire can be designed as a flat round wire or as a wire with a different cross section.
[0048] The at least one precious metal wire may have a two-dimensional structure or a three-dimensional structure. The at least one precious metal wire may include, for example, one or more wavy, stepped or spiral longitudinal sections over its entire length or may be formed as a wavy, stepped or spirally curved line. If the at least one precious metal wire includes a spiral longitudinal section, both the active catalyst surface of the catalyst mesh and the quality of the catalyst mesh can be adjusted relative to the surface unit via the number of windings of the spiral longitudinal section. When a precious metal wire having a two-dimensional structure or a three-dimensional structure is used, the catalyst mesh made therefrom will have a three-dimensional structure; for its long-term stability, the use of dispersion-hardened precious metal alloys has proven to be particularly advantageous.
[0049] The at least one noble metal wire may comprise a plurality of wires, in which case also referred to as filaments. In such cases, the at least one noble metal wire may have increased strength, which improves the long-term stability of the catalyst mesh. The filaments may all consist of the same material, i.e., all contain a noble metal, or of different materials, without necessarily all containing a noble metal.
[0050] The filaments may be twisted together; in these cases, the at least one noble metal wire comprises a rope-like structure. It may also be advantageous if the at least one noble metal wire comprises at least one filament, which is helically wound around at least one further filament.
[0051] The at least one noble metal wire may comprise at least one filament made of a dispersion-strengthened noble metal alloy and at least one further filament made of a non-dispersion-strengthened noble metal alloy. Specifically, the at least one noble metal wire may comprise at least one filament made of a dispersion-strengthened platinum alloy and at least one further filament made of a non-dispersion-strengthened platinum alloy. It has been shown that a catalyst mesh comprising such noble metal wires is particularly advantageous for the long-term stability and simultaneous high catalytic efficiency of a catalyst mesh comprising at least one linear filament and at least one spiral filament arranged around it.
[0052] In many cases, it may be advantageous if the catalyst mesh comprises at least one further noble metal wire, i.e. is formed from two or more noble metal wires. In these cases, the at least two noble metal wires may consist of the same material or of different materials. The at least two noble metal wires may have the same or different diameters and / or the same or different structures. It has proven to be advantageous if the at least one further noble metal wire comprises a platinum alloy, in particular a non-dispersion strengthened platinum alloy.
[0053] The catalyst mesh according to the invention is suitable for preparing nitric acid by the Ostwald process. An ammonia-oxygen mixture flows through the catalyst mesh for catalytic combustion of ammonia.
[0054] The catalyst mesh according to the invention is also suitable for the preparation of hydrocyanic acid by the Andrussow process. An ammonia-methane-oxygen mixture flows through the catalyst mesh.
[0055] The invention also relates to a catalyst system for the catalytic oxidation of ammonia, comprising at least one catalyst mesh according to the invention. With regard to preferred embodiments of the catalyst mesh, reference is made to the preceding description.
[0056] Preferably, the catalyst system comprises a catalyst mesh stack; in other words, the catalyst system comprises at least two catalyst meshes. The at least two catalyst meshes may be identical or different. Depending on the intended use of the catalyst system and the reaction conditions in the flow reactor, catalyst meshes having different or identical structures and different or identical noble metal wires may be combined with each other.
[0057] The catalyst system may comprise one or more catalyst mesh groups. A catalyst mesh group is understood to mean a collection of catalyst meshes formed by at least one noble metal wire having the same composition. Typically, a catalyst mesh group comprises more than one catalyst mesh.
[0058] The catalyst system may also include additional components.
[0059] In a preferred embodiment, the catalyst system may include a separator element, for example, in the form of an intermediate net. Such separator elements may be used to resist compression and / or melting or sintering of adjacent catalyst nets or catalyst net groups under pressure loads. Compared to the catalyst net, the separator element preferably has limited flexibility.
[0060] Suitable separator elements are, for example, elements or meshes made of heat-resistant steel, typically a FeCrAl alloy such as Megapyr or Kanthal, stainless steel or a heat-resistant alloy such as a nickel-chromium alloy. One or more separator elements may also comprise a catalytically active coating comprising at least one noble metal.
[0061] The invention also relates to a method for the catalytic oxidation of ammonia, in which a fresh gas containing ammonia is conducted over a catalyst mesh according to the invention. With regard to preferred embodiments of the catalyst mesh, reference is made to the preceding description.
[0062] The invention is explained below with reference to the accompanying drawings, compression tests and experiments on catalytic efficiency.
[0063] Figure 1A vertically positioned flow reactor 1 for the heterogeneously catalytic oxidation of ammonia is schematically shown. The catalyst system 2 forms the actual reaction zone of the flow reactor 1. The catalyst system 2 comprises a plurality of catalyst nets 4 arranged one behind the other in the flow direction 3 of the fresh gas, and behind which a plurality of capture nets 5 may be arranged. The effective catalyst net diameter may be up to 6 m. The nets used are in each case textile fabrics produced by weaving or braiding of precious metal threads.
[0064] A corresponding flow reactor is used, for example, for the synthesis of hydrocyanic acid according to the Andrussow process. As fresh gas, an ammonia-methane-air mixture is introduced under elevated pressure in the flow direction 3. Upon entering the catalyst system 2, the gas mixture is ignited and subsequently an exothermic combustion reaction occurs. The overall reaction is:
[0065] NH3+CH4+1.5O2→HCN+3H2O
[0066] This exothermic reaction raises the temperature of the gas to up to 1100°C.
[0067] Compression test
[0068] The catalyst mesh was woven from threads with a diameter of 76 μm. A linear warp with 17.5 turns / cm and a spiral weft were used. Figure 2 The structure of the helical wire is shown. Both wires contain PtRh10 alloy, a standard industrial alloy. In the case of the catalyst mesh according to the invention, the helical wire is dispersion strengthened.
[0069] At an ambient temperature of 1200°C, a stack of 24 catalyst nets (L×W: 50 mm×50 mm) was subjected to a weight of 1 kg each over a period of 3 days. The thickness of the net stack was measured at 16 points before and after the heat treatment. At the start of the test, the two net packages had a thickness of about 8 mm. The compression was determined according to the following formula:
[0070]
[0071] The results of the compression tests are compared in Table 1. The mesh packs (EB) using the catalyst mesh according to the invention show significantly lower compression than the mesh packs where the mesh is made entirely of non-dispersion reinforced standard wire (VB).
[0072] Table 1 :
[0073] compression[%] VB 40.5% EB 22.5%
[0074] The use of dispersion-strengthened platinum wires improves the compression stability of the tested catalyst mesh packages, which is expected to have a positive effect on the long-term efficiency of the corresponding catalyst system.
[0075] Efficiency in flow reactors
[0076] In such Figure 1 In the flow reactor shown in , the efficiency of a catalyst system consisting of 10 catalyst meshes, each of which has a composition similar to that in the comparative example and the example according to the present invention involving the oxidation of ammonia, is compared.
[0077] Fresh gas is introduced from above into the reactor 1 at elevated pressure. The fresh gas is an ammonia-air mixture with a nominal ammonia content of 10.7% by volume and a preheat temperature of 175° C. Upon entering the catalyst system 2, the gas mixture is ignited, whereupon an exothermic combustion reaction occurs. The following main reactions occur:
[0078] 4NH3+5O2→4NO+6H2O
[0079] In this case, ammonia (NH3) is converted into nitrogen monoxide (NO) and water (H2O). The nitrogen monoxide (NO) formed reacts with excess oxygen in the outflowing reaction gas mixture (symbolized by the directional arrow 7 indicating the flow direction of the outflowing reaction gas mixture) to form nitrogen dioxide (NO2), which reacts with water in the downstream absorption system to form nitric acid (HNO3).
[0080] The catalytic efficiency (i.e., product yield of NO) is measured in the following order:
[0081] 1. Ensure that the catalyst system is suitable for complete conversion of the ammonia used. This means that no significant amounts of NH 3 are present in the product gas anymore, which is checked by means of mass spectrometry of the product gas.
[0082] 2. The NH3 / air sample upstream of the catalyst packing and the sample from the downstream product gas are removed simultaneously in respective independent evacuation pistons. The mass of the gas is determined by weighing.
[0083] 3. The NH3 / air mixture is taken up in distilled water and, after a color change, titrated with 0.1 N sulfuric acid and methyl red.
[0084] 4. The nitrous acid product gas was taken up in 3% sodium peroxide solution and, after a color change, titrated with 0.1 N sodium hydroxide solution and methyl red.
[0085] 5. Catalytic efficiency Eta is generated by the following formula: Eta = 100 × C n / C a , where C a is the average NH3 concentration in the fresh gas from seven separate measurements, expressed as weight percent, and C n is the average NO of 7 individual measurements xconcentration, which is expressed as the amount of NO that has been oxidized to form x The weight percentage of NH3.
[0086] 6. Separately, the volume fraction of N2O in the product gas was determined by means of gas chromatography.
[0087] Table 2 compares the catalyst efficiency (NO production, %) of the catalyst system at different fresh gas flow rates. Abbreviation “tN / m 2 "d" stands for "tons of nitrogen (from ammonia) per square meter of normalized effective cross-sectional area of the catalyst system per day".
[0088] Table 2 :
[0089]
[0090] Both test systems showed comparable catalytic efficiency at all tested fresh gas flow rates. The results show that the use of dispersion-strengthened platinum alloys does not impair the catalytic activity of the catalyst mesh.
Claims
1. A catalyst mesh comprising at least one noble metal wire, It is characterized in that The at least one precious metal wire comprises at least one dispersion-strengthened precious metal alloy, wherein the precious metal alloy comprises at least one non-precious metal in addition to at least one precious metal, wherein the at least one non-noble metal is selected from the group consisting of zirconium, cerium, scandium and yttrium, and the at least one non-noble metal is at least partially present as an oxide. The catalyst mesh according to claim 1 , wherein the catalyst mesh has a three-dimensional structure.
3. The catalyst mesh according to claim 1 or 2, wherein the proportion of the at least one noble metal is at least 50% by weight, based on the total weight of the dispersion-strengthened noble metal alloy.
4. The catalyst web according to any one of the preceding claims, wherein the dispersion strengthened precious metal alloy consists of the at least one precious metal, an at least partially oxidized non-precious metal and impurities.
5. The catalyst mesh according to any one of the preceding claims, wherein the at least one precious metal is selected from the group consisting of platinum, palladium, rhodium and mixtures thereof.
6. The catalyst web according to any one of the preceding claims, wherein the dispersion strengthened precious metal alloy is a platinum alloy.
7. The catalyst web according to any one of the preceding claims, wherein the dispersion strengthened precious metal alloy contains 0.005 wt. % to 1.0 wt. % of the at least one non-precious metal.
8. The catalyst web according to any one of the preceding claims, wherein the at least one non-precious metal is at least 70% oxidized.
9. The catalyst mesh according to any one of the preceding claims, wherein the at least one noble metal wire comprises a plurality of filaments.
10. The catalyst mesh according to any one of the preceding claims, wherein the at least one noble metal wire has a two-dimensional structure or a three-dimensional structure.
11. The catalyst mesh of claim 10, wherein the at least one noble metal wire comprises a helical longitudinal portion.
12. The catalyst mesh according to any one of the preceding claims, wherein the catalyst mesh comprises at least one further noble metal wire.
13. The catalyst mesh of claim 12, wherein the at least one additional noble metal wire comprises a platinum alloy.
14. A catalyst system for the catalytic oxidation of ammonia, comprising at least one catalyst mesh according to any one of the preceding claims. 15 . A method for the catalytic oxidation of ammonia, wherein a fresh gas containing ammonia is conducted over at least one catalyst mesh according to claim 1 .
